An old friend with a new face: tRNA-derived small RNAs with big regulatory potential in cancer biology - Di Fazio, A; Gullerova, M (Springer Nature, 2023)
Transfer RNAs (tRNAs) are small non-coding RNAs (sncRNAs) essential for protein translation. Emerging evidence suggests that tRNAs can also be processed into smaller fragments, tRNA-derived small RNAs (tsRNAs), a novel class of sncRNAs with powerful applications and high biological relevance to cancer. tsRNAs biogenesis is heterogeneous and involves different ribonucleases, such as Angiogenin and Dicer. For many years, tsRNAs were thought to be just degradation products. However, accumulating evidence shows their roles in gene expression: either directly via destabilising the mRNA or the ribosomal machinery, or indirectly via regulating the expression of ribosomal components. Furthermore, tsRNAs participate in various biological processes linked to cancer, including apoptosis, cell cycle, immune response, and retroviral insertion into the human genome. It is emerging that tsRNAs have significant therapeutic potential. Endogenous tsRNAs can be used as cancer biomarkers, while synthetic tsRNAs and antisense oligonucleotides can be employed to regulate gene expression. In this review, we are recapitulating the regulatory roles of tsRNAs, with a focus on cancer biology.